Consumer behavior: an investigation into how motivational factors influence online consumers’ impulse purchases of fashion items - Mahomed, Asiya (University of the Witwatersrand, Johannesburg, 2024)
The global growth of online retail in the last decade has played a major role in altering consumer behavior. A key behavioral trend has been the rise of ‘impulsive buying’, a phenomenon that continues to grow significantly in South Africa in particular. However, in part due to its novelty and rapid emergence during and after COVID-19, the nature of and the decision-making processes behind online impulsive buying have been largely unexplored. Both retailers and marketers alike have therefore sought to understand its role in order to maximize market potential. As such, this study aims to provide new insight by building on existing literature about online consumer behavior. It determines the motivations that influence impulsive buying in online retail fashion consumers, as well as how their level of involvement or interest in fashion influences their decision-making. Using a deductive, quantitative approach and collecting data sets through survey questionnaires of 510 millennial South African consumers, the study focuses on two types of motivational factors; Utilitarian and Hedonic, in order to understand the phenomenon. Applying a moderation model, the study uses statistical analysis to demonstrate that fashion involvement can act as a moderating variable that could influence the relationship between the two factors and impulsive buying behavior. It finds that fashion involvement has a negative relationship with the utilitarian effects of price, and the hedonic effects of sensory and stimulation elements. As the regression co-efficient for these interactions is closer to zero (p<.05 or lower) with a 3-4 % variance in impulse product purchase in the macro model used, the study indicates that the impact of these elements on impulsive buying decreases as a consumer’s level of interest in fashion increases. The research ultimately contributes to the literature by explaining these relationships through the moderation model and its theoretical underpinnings. Despite its focus on a small data set drawn from the South African context, it is hoped that the study’s findings may encourage further research on a wider scale, and help marketers and online retailers develop and improve the practical efficiency of their online marketing strategies to harness impulsive buying behavior.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: impulse buying; Hedonic; Utilitarian; Fashion involvement; e-commerce; COVID-19; UCTD; SDG-8: Decent work and economic growth